OBESITY AS A RISK FACTOR FOR SURGICAL SITE INFECTION AFTER TRANSPERITONEAL CESAREAN SECTION - Rahayu, Rahayu (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2018)
Surgical site infection (SSI) is one of the main complications that can increase morbidity and mortality in obese women after cesarean section. Surgical site infection can be caused by endogenous or exogenous factors. This was a case ofÂ a woman, G4P3A0, 32 years, afterÂ trans-peritoneal cesarean section for indications of breech presentation; primary uterine inertia; premature rupture + 22 hours with BMI = 30.80 kg/m2. This case report discusses how obesity causes surgical site infection and its management.